The Decoy Effect as a Nudge: Boosting Hand Hygiene With a Worse Option. (January 2019) - Li, Meng; Sun, Yan; Chen, Hui
This article provides the first test of the decoy effect as a nudge to influence real-world behavior. The decoy effect is the phenomenon that an additional but worse option can boost the appeal of an existing option. It has been widely demonstrated in hypothetical choices, but its usefulness in real-world settings has been subject to debate. In three longitudinal experiments in food-processing factories, we tested two decoy sanitation options that were worse than the existing sanitizer spray bottle. Results showed that the presence of a decoy, but not an additional copy of the original sanitizer bottle in a different color, drastically increased food workers' hand sanitizer use from the original sanitizer bottle and, consequently, improved workers' passing rate in hand sanitation tests from 60% to 70% to above 90% for 20 days. These findings indicate that the decoy effect can be a powerful nudge technique to influence real-world behavior.